Electrochemical impedance analysis of perovskite–electrolyte interfaces. Issue 16 (9th February 2017) - Li, Zhen; Mercado, Candy C.; Yang, Mengjin; Palay, Ethan; Zhu, Kai
Abstract : The flat band potentials and carrier densities of spin coated and sprayed MAPbI3, FA0.85 Cs0.15 PbI3, and MAPbBr3 perovskite films were determined using the Mott–Schottky relation. Abstract : The flat band potentials and carrier densities of spin coated and sprayed MAPbI3, FA0.85 Cs0.15 PbI3, and MAPbBr3 perovskite films were determined using the Mott–Schottky relation. The films developed a space charge layer and exhibited p-type conduction with a carrier concentration of ∼10 16 cm −3 for spin coated films. Electrochemical impedance spectra showed typical space charge impedance at frequencies >1 kHz, and an exceptional high capacitance at frequency <1 kHz owing to an ion diffusion component.